Characterization and Hydrogen Storage Capacity Analysis of Dip Coated Lithium Aluminium Hydride Thin Films - Chusak Choawarot; Vilailuck Siriwongrungson; Janjira Hongrapipat; Shu Sheng Pang; Michael Messner (Materials science forum, 2021)
Complex metal hydrides are one of the most effective hydrogen storage materials due to their unique property to absorb and desorb hydrogen with the hydrogen storage capacity of about 5-7 wt%. In this study, lithium aluminium hydride (LiAlH 4 ) was coated on glass substrate using dip coating method. The coating conditions investigated were LiAlH 4 concentrations of 6 g/l, 10 g/l and 20 g/l and post-annealing time from 0 to 60 min. Phase and grain size of the deposited LiAlH 4 were analyzed using X-ray powder diffraction (XRD). Scanning electron microscope (SEM) was used for surface morphology analysis. The hydrogen storage capacity of the deposited thin films was analyzed using thermogravimetric analysis (TGA). The experimental results revealed that the phase of the deposited LiAlH 4 thin films on glass substrate were mixed with lithium aluminium hydroxide hydrate (LiAl 2 (OH) 7 ·2H 2 O) and lithium hexahydroaluminate (Li 3 AlH 6 ). The intensity of the LiAl 2 (OH) 7 ·2H 2 O and LiAlH 4 peaks tends to decrease with increasing LiAlH 4 concentration and post-annealing time while the intensity of the Li 3 AlH 6 peaks increased with increasing LiAlH 4 concentration and post-annealing time. The grain size was decreased with increasing LiAlH 4 concentration and post-annealing time. The smaller grain size the better the hydrogen storage capacity. The hydrogen storage capacity of the deposited LiAlH 4 thin film was increased from 0.124 wt % using LiAlH 4 concentration of 6 g/l without post-annealing to 1.675 wt % using LiAlH 4 concentration of 20 g/l with 60 min post-annealing time.
Keywords: Hydrogen Storage and Materials; Hybrid Renewable Energy Systems; Ammonia Synthesis and Nitrogen Reduction